Current Status of Consumer Education in High Schools in the Kinki Region and Issues of Cooperation - Matsubara, Yuka; Noguchi, Miki; Yoshii, Minako; Suzuki, Mayuko; Ide, Nao; Komaki, Mie (Journal of Japan Academy of Consumer Education, 2023)
This study attempts to clarify the current status of consumer education in high schools in the Kinki region of Japan, and the needs and issues regarding cooperation and cooperation between high school teachers, CEC, and other organizations.The research methods included a questionnaire survey and remotely conducted interview surveys targeting teachers in charge of consumer education at high schools in the six prefectures of the Kinki region. The results of the study show that there were a few cases where high schools had a person in charge of consumer education. Further, even in subject studies (home economics and civics) which are supposed to be implementing consumer education, the implementation rate was not 100%. In addition, the low awareness of the CEC clearly indicates that enhancing the significance of the CEC is needed to enable it to communicate the specific needs of school teachers and others to companies and organizations.